The Influence of Social Media Marketing and Affiliate Marketing on Willingness to Buy on Shopee in Medan City (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study seeks to examine the impact of Social Media Marketing and Affiliate Marketing on Purchase Intent on the Shopee platform in Medan City. The research employed a quantitative methodology via a survey of 384 Shopee user respondents. We used Partial Least Square Structural Equation Modeling (SEM-PLS) to analyze the data. The findings indicated that Social Media Marketing exerts a positive and significant influence on Willingness to Buy, evidenced by a coefficient value of 0.104 (T-statistic = 2.987; P-value = 0.003). Affiliate Marketing likewise has a positive and substantial effect on Willingness to Buy, with a coefficient value of 0.284 (T-statistic = 5.947; P-value = 0.000). The study's findings suggest that management of e-commerce platforms like Shopee should make the most of social media to reach more people and get more people involved. Also, working with the correct affiliate partners can make product suggestions stronger and bring in more customers, which can lead to a big increase in sales conversions.